Pengaruh Penambahan Ekstrak Jeruk Manis (Citrus Sinensis) Terhadap Kualitas Fisik Yoghurt Susu Sapi - Majid, Irmawaty; Furwani, Diyaz; Hidayat, Muhammad Nur; Ananda, Suci; Lestari, Ayu; Asgaf, Khaifah (Universitas Islam Negeri Alauddin Makassar, 2026)
Sweet orange extract contains high vitamin C so it has the potential to be used in making yogurt to increase the vitamin C content in the product. This study aims to reveal the effect of variations in the concentration of sweet orange extract (Citrus sinensis) on the physical properties of cow's milk yogurt. The study used a Completely Randomized Design (CRD) with 4 treatments and 3 replications consisting of yogurt without additional extract (P0), the addition of sweet orange extract 3% (P1), 5% (P2), and 7% (P3). The data obtained were analyzed by analysis of variance (ANOVA) with levels of 5% and 1% and continued with the Least Significant Difference Test (LSD). The parameters observed included pH, viscosity, and texture. The results showed that the addition of sweet orange extract had a significant effect on the pH value of yogurt with pH values ​​ranging from 5.20 - 4.42, but did not significantly affect (P>0.05) the viscosity value of yogurt with values ​​ranging from 1.53 - 3.30. Meanwhile, the visualization results of the yogurt texture showed a variety of textures, from thick to not thick. Thus, the best results in this study were obtained with the addition of 3% sweet orange extract.